2015
DOI: 10.1615/plasmamed.2016015752
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plasma Treatment in Open Air on Mycotoxin Content and Grain Nutriments

Abstract: Surface treatment by low-temperature plasma has a great potential in a wide range of applications in many industries and research fields, such as material engineering, automobile industry, ecology, medicine, and agriculture. The application of plasma treatments is relatively new and not very common in agriculture. Protecting cereal seeds against some fungal diseases is one of the plasma applications in agriculture. We tested the possibility of decreased mycotoxin concentration by low pressure and atmospheric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…The changes of dry matter content were related to evaporation of water after the plasma treatment, since the temperature of the samples after radiation were raised ( Figure 5). Similar findings were reported by Kriz et al [35] who studied plasma treatment of grain and Selcuk et al [36] who studied impact of plasma on grain and legumes. Moreover, all the changes were significantly (p < 0.05) different in comparison to control samples.…”
Section: Dry Matter Content and Water Activitysupporting
confidence: 85%
“…The changes of dry matter content were related to evaporation of water after the plasma treatment, since the temperature of the samples after radiation were raised ( Figure 5). Similar findings were reported by Kriz et al [35] who studied plasma treatment of grain and Selcuk et al [36] who studied impact of plasma on grain and legumes. Moreover, all the changes were significantly (p < 0.05) different in comparison to control samples.…”
Section: Dry Matter Content and Water Activitysupporting
confidence: 85%
“…Low penetration depth of CAPP protects nutrients in bulk material from degradation, limiting degradation to a thin surface layer [19]. Kříž et al [20,21] showed that the content of proteins and fibers as well as residual dry matter, nitrogen-free extract, fat and ash in intact barley grains were not significantly affected by treatment with CAPP while the content of selected mycotoxins was reduced by 20%–70%. We hypothesize that the confinement of mycotoxin contamination to the surface of grains accounted for the selectivity of the degradation in this study.…”
Section: Introductionmentioning
confidence: 99%
“…CP studies have shown potential inhibition of fungal growth and degradation of mycotoxins. The study of peanuts, cereals for human and animal consumption, malted barley seeds, maize, hazelnuts, and date palm has shown the potential of CP for fungal inactivation and degradation of several mycotoxins [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. The emerging use of CP for fungi inactivation and mycotoxin degradation will be very useful in ensuring mycotoxin-free globally.…”
Section: Emerging Cp Treatment For Removal Of Mycotoxinmentioning
confidence: 99%